1991
DOI: 10.1159/000243344
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose of Labetalol in Normotensive Pregnancy: Effects on Maternal Hemodynamics and Uterine and Fetal Flow Velocity Waveforms

Abstract: The short-term effect of 0.8 mg/kg of intravenous bolus of labetalol upon maternal and fetal hemodynamics was investigated in 10 healthy women at 38 weeks of gestation admitted to the hospital for elective cesarean section. The maximum effect occurred within 35 min after labetalol. At that point, the mean arterial pressure had decreased by 16%, and a slight decrease was observed in maternal heart rate. As to the flow velocity waveforms, no significant change was found in mean systolic/diastolic (S/D) ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
2
7
1
Order By: Relevance
“…The antihypertensive effect of labetalol in the hypertensive subjects was clear: the nadir of BP occurred 30 -35 minutes after labetalol infusion. In a study with normotensive subjects the drop in BP followed the same time course [7]. The mean drop in MAP was 18% which agrees with previous studies with the same dose of labetalol [5,11] and also with our previous study with normotensive subjects [7].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The antihypertensive effect of labetalol in the hypertensive subjects was clear: the nadir of BP occurred 30 -35 minutes after labetalol infusion. In a study with normotensive subjects the drop in BP followed the same time course [7]. The mean drop in MAP was 18% which agrees with previous studies with the same dose of labetalol [5,11] and also with our previous study with normotensive subjects [7].…”
Section: Discussionsupporting
confidence: 90%
“…In a study with normotensive subjects the drop in BP followed the same time course [7]. The mean drop in MAP was 18% which agrees with previous studies with the same dose of labetalol [5,11] and also with our previous study with normotensive subjects [7]. The antihypertensive effect remained measurable for more than one hour.…”
Section: Discussionsupporting
confidence: 90%
“…Nifedipine readily crosses the placenta with a maternal/ fetal plasma ratio of 0.93. 3 Despite significant changes in maternal haemodynamics we could not demonstrate any changes in the uterine, umbilical or middle cerebral pulsatility indices or time-averaged maximum velocities. This suggests that nifedipine has no effect on the uteroplacental or fetal circulation but the limitations of both measurements in reflecting total blood flow should be noted.…”
Section: Discussioncontrasting
confidence: 54%
“…2,9 Another study observed a significant decrease in uterine artery resistance but without changes in the arcuate or umbilical artery Doppler flows. 3 The absence of changes in the uterine circulation is remarkable considering the substantial maternal afterload reduction. It indicates that in healthy normotensive pregnancy without signs of placental insufficiency, trophoblast invasion has lowered downstream resistance to such an extent that nifedipine is unable to further reduce uterine resistance, despite its potency to reduce the systemic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation